Ex vivo gut cultures of Aedes aegypti are efficiently infected by mosquito-borne alpha- and flaviviruses - Ana Lucia Rosales Rosas; Lanjiao Wang; Sara Goossens; Arno Cuvry; Li-Hsin Li; Nanci Santos-Ferreira; Alina Soto; Kai Dallmeier; Joana Rocha-Pereira; Leen Delang (Microbiology Spectrum, 2023)
ABSTRACT Aedes aegypti mosquitoes can transmit several arboviruses, including chikungunya virus (CHIKV), dengue virus (DENV), and Zika virus (ZIKV). When blood-feeding on a virus-infected human, the mosquito ingests the virus into the midgut (stomach), where it replicates and must overcome the midgut barrier to disseminate to other organs and ultimately be transmitted via the saliva. Current tools to study mosquito-borne viruses (MBVs) include 2D-cell culture systems and in vivo mosquito infection models, which offer great advantages, yet have some limitations. Here, we describe a long-term ex vivo culture of Ae. aegypti guts. Cultured guts were metabolically active for 7 d in a 96-well plate at 28°C and were permissive to ZIKV, DENV, Ross River virus, and CHIKV. Ex vivo guts from Culex pipiens mosquitoes were found to be permissive to Usutu virus. Immunofluorescence staining confirmed viral protein synthesis in CHIKV-infected guts of Ae. aegypti. Furthermore, fluorescence microscopy revealed replication and spread of a reporter DENV in specific regions of the midgut. In addition, two known antiviral molecules, β-d-N4-hydroxycytidine and 7-deaza-2′-C-methyladenosine, were able to inhibit CHIKV and ZIKV replication, respectively, in the ex vivo model. Together, our results show that ex vivo guts can be efficiently infected with mosquito-borne alpha- and flaviviruses and employed to evaluate antiviral drugs. Furthermore, the setup can be extended to other mosquito species. Ex vivo gut cultures could thus be a new model to study MBVs, offering the advantage of reduced biosafety measures compared to infecting living mosquitoes. IMPORTANCE Mosquito-borne viruses (MBVs) are a significant global health threat since they can cause severe diseases in humans, such as hemorrhagic fever, encephalitis, and chronic arthritis. MBVs rely on the mosquito vector to infect new hosts and perpetuate virus transmission. No therapeutics are currently available. The study of arbovirus infection in the mosquito vector can greatly contribute to elucidating strategies for controlling arbovirus transmission. This work investigated the infection of guts from Aedes aegypti mosquitoes in an ex vivo platform. We found several MBVs capable of replicating in the gut tissue, including viruses of major health importance, such as dengue, chikungunya, and Zika viruses. In addition, antiviral compounds reduced arbovirus infection in the cultured gut tissue. Overall, the gut model emerges as a useful tool for diverse applications such as studying tissue-specific responses to virus infection and screening potential anti-arboviral molecules.